Paediatric Postoperative Intussusception - Shrestha, Sundar; Basnet, Bal Mukunda; Thapa, Anupama (Journal of Nepal Health Research Council, 2019)
Intussusception is one of the common causes of acute abdomen in early childhood, particularly in children younger than two years of age. The majority of cases in children are idiopathic. Pathologic lead points can be identified in only 25 percent of cases. Here. we present a case of 15 months female child with Ileoileal postoperative intussusception with an anastomotic margin as a lead point, following resection anastomosis done for patent vitello intestinal duct. Role of high clinical suspicion, investigations and judgement are highlighted in managing the case. Keywords: Anastomosis; ileoileal; postoperative intussusception; patent vitello-intestinal duct.